THE IMPLICATIONS OF CCR DEC. NO. 643/2024 ON THE NOTION OF PUBLIC GUARDIANSHIP - Marta-Claudia CLIZA (Challenges of the Knowledge Society, 2025)
This study targets the interpretation of CCR dec. no. 643/2024 given to the notion of public guardianship, more precisely by redefining the area of the authorities that fall under the control of the Prefect in terms of the legality of the acts issued by such authorities. Therefore, starting from the exemplification referred to in art. 123 para. (5) of the Constitution, the issue that arises is whether the acts issued by the President of the County Council can be appealed before the Court of Contentious Administrative by the Prefect. Starting from these premises, the study analyses the notion of public guardianship, that of local and county authorities and concludes on the construction of the Constitutional Court in a critical way.